Health literacy for people living with HIV/Aids: an integrative review - Gilmara Holanda da Cunha; Marli Teresinha Gimeniz Galvão; Patrícia Neyva da Costa Pinheiro; Neiva Francenely Cunha Vieira
ABSTRACT Objective: to analyze knowledge produced by research about health literacy for adult with HIV/Aids. Method: an integrative literature review, using six databases, was conducted between January and April of 2014. The descriptors aids and Health Literacy were used, in Portuguese, English and Spanish. A total of 130 articles were found and 14 were selected. Three categories were identified: educational technologies and health literacy for HIV/Aids; assessment of health literacy of patients with HIV/Aids; and health literacy and adherence to antiretroviral therapy. Results: analysis of health literacy, socioeconomic status and educational level of people living with HIV/ Aids was essential for implementation of educational strategies that increased adherence to health guidance. Conclusion: this study showed the importance of health literacy for working with people living with HIV/Aids, especially considering individuals who did not possess the minimum necessary for survival, which makes it relevant and encourages further research on the topic.